Gestión del talento humano y su incidencia en la calidad del servicio al cliente en la Cooperativa San Miguel Ltda., en el año 2025. - Estrada Arias, Landy Johana (2025)
The purpose of this research is to evaluate the relationship between human talent management and customer service quality at Cooperativa San Miguel Ltda., located in San Miguel canton, Bolivar province, during the year 2025. A mixed approach was adopted under a non- experimental design, applying the hypothetical-deductive method, together with descriptive and explanatory techniques. Data were collected through surveys applied to 331 members and 25 employees of the cooperative, using instruments with a Likert scale and closed questions. The data were analyzed using Excel and SPSS programs, applying Cronbach's alpha coefficient to validate the reliability of the instruments, and the Chi-square test to contrast the hypothesis proposed. The results showed deficiencies in key areas of human talent management, such as selection, training, motivation, rotation and performance evaluation, negatively affecting the perception of service. It is concluded that adequate human talent management has a positive impact on the work environment, strengthens institutional commitment and improves the quality of customer service. Finally, a comprehensive human talent management model based on continuous training, recognition, retention and collaborative leadership is proposed.